2016
DOI: 10.1021/acs.jpcb.6b00781
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Molecular Dynamics Study on Tri-n-butyl Phosphate in Organic and Aqueous Environments and Its Relevance to Nuclear Extraction Processes

Abstract: A refined model for tri-n-butyl phosphate (TBP), which uses a new set of partial charges generated from our ab initio density functional theory calculations, has been proposed in this study. Molecular dynamics simulations are conducted to determine the thermodynamic properties, transport properties, and the microscopic structures of liquid TBP, TBP/water mixtures, and TBP/n-alkane mixtures. These results are compared with those obtained from four other TBP models, previously described in the literature. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 63 publications
3
43
0
Order By: Relevance
“…Numerous simulation studies have used different TBP force fields to investigate TBPwater interactions. 23,38,40 Accurate simulation of those interactions at an aqueous/organic interface or in a bulk alkane-based solution have required either a small degree of TBP charge scaling 23,24,38 or explicit polarization. 40 Accurate prediction of the interfacial tension requires careful calibration of the surfactant polarity which may be at odds with optimizations made for reproducing bulk phase properties.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous simulation studies have used different TBP force fields to investigate TBPwater interactions. 23,38,40 Accurate simulation of those interactions at an aqueous/organic interface or in a bulk alkane-based solution have required either a small degree of TBP charge scaling 23,24,38 or explicit polarization. 40 Accurate prediction of the interfacial tension requires careful calibration of the surfactant polarity which may be at odds with optimizations made for reproducing bulk phase properties.…”
Section: Resultsmentioning
confidence: 99%
“…The sample solution was loaded using a peristaltic pump into a titanium cell with a thickness of 1.25 mm (path length) and quartz plate windows (6.0 mm × 2.5 mm × 0.02 mm). 51,53 All X-ray scattering data were acquired at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The AMBER-based force field for TBP has been optimized by Ye et al 42 for the interfacial water/n-alkane system to accurately reproduce the experimentally determined extracted water concentration in the organic phase at equilibrium. 38,42 System compositions, simulation methodology and force field descriptions are given in the Supporting Information. Additional data using alternative force fields are presented in Supporting Information and validate that key results are independent of the force field employed.…”
Section: Computational Methods Simulation Systems and Force Fieldsmentioning
confidence: 99%
“…22,28,31 In this work the surfactant tri-n-butyl phosphate (TBP) is chosen because of its ubiquity in solvent extraction applications, 1,32 notably in the Plutonium Uranium Reduction EXtraction (PUREX) process, and because it has been the topic of extensive study in the MD modeling literature. 8,10,20,[33][34][35][36][37][38][39][40][41][42] Prior work 7,20,42,43 has shown that TBP adsorbs to the water/organic interface with its dipole orthogonal and alkyl tails parallel to the interface plane. While the extraction of water from the interface by TBP has been qualitatively described in the literature, 7,42 it remains to be understood -either qualitatively or quantitatively -how TBP adsorption influences the capillary wave front, including its heterogeneity, fluctuations in space, and the resulting mechanisms for water extraction into the organic phase.…”
Section: Introductionmentioning
confidence: 99%